Trade Interference or Good Environmental Stewardship: The Case of Gibson Guitar and the Lacey Act - Rarick, Charles (American Journal of Trade and Policy, 2015)
The Gibson Guitar Corporation based in Tennessee was raided by federal agents twice for importing prohibited wood products. The raids, especially the second, attracted much public attention and have even led for calls from some members of Congress for a change. The case examines the Lacey Act, the allegations of wrong doing, and the question trade and domestic job creation at the expense of environmental stewardship. JEL Classifications Code: F18